Case report: A de novo Non-sense SOX9 mutation (p.Q417*) located in transactivation domain is Responsible for Campomelic Dysplasia - Qiao, Xingxing; Wu, Liping; Tang, Jianjun; Xiang, Rong; Fan, Liangliang; Huang, Hao; Chen, Yaqin (Frontiers in Pediatrics, 2023)
Background: Campomelic dysplasia (CD) is an autosomal dominant skeletal dysplasia syndrome characterized by shortness and bowing of lower extremities, and often accompanied by XY sex reversal. Heterozygous pathogenic variants of SOX9 or rearrangement involving the long arm of chromosome 17 are the causes of disease. However, evidence for pathogenesis of SOX9 haploinsufficiency is insufficient. Methods: We enrolled a Chinese family where the fetus was diagnosed with CD. The affected fetus was selected for whole-exome sequencing to identify the pathogenic mutations in this family. Results: After data filtering, a novel non-sense SOX9 variant (NM_000346.3；c.1249C > T；p.Q417*) was identified as the pathogenic lesion in the fetus. Further co-segregation analysis using Sanger sequencing confirmed that this novel SOX9 mutation (c.1249C > T；p.Q417*) was a de novo mutation in the affected fetus. This terminated codon mutation identified by bioinformatics was located at an evolutionarily conserved site of SOX9. The bioinformatics-based analysis predicted this variant was pathogenic and affected SOX9 transactivation activity. Conclusion: CD is a rare condition, which connected with SOX9 tightly. We identified a novel heterozygous SOX9 variant (p.Q417*) in a Chinese CD family. Our study supports the putative reduced transactivation of SOX9 variants in the pathogenicity of CD.